Search source of above-standard pollutions by monitoring of industrial stocks - Мезиненко, А. Є.; Манакова, Н. О. (Eastern-European Journal of Enterprise Technologies, 2012)
In the paper the questions related to the optimization of City Sanitation Service through the introduction of continuous monitoring of industrial effluents. This will speed up the search for the source of excessive pollution, monitor the qualitative composition and amount of runoff